J-aggregates albumin-based NIR-II fluorescent dye nanoparticles for cancer phototheranostics. (December 2022) - Du, Bulin; Liu, Ruiqi; Qu, Chunrong; Qian, Kun; Suo, Yongkuan; Wu, Fengxia; Chen, Hongda; Li, Xuena; Li, Yaming; Liu, Hongguang; Cheng, Zhen
Abstract: Phototheranostics, relying on energy conversions of fluorophores upon excitation, integrating diagnostic fluorescence imaging and photo-driven therapy, represents a promising strategy for cancer precision medicine. Compared with the first near-infrared biological window (NIR-I), fluorophores imaged in the second window (NIR-II, 1000–1700 ​nm) exhibit a higher temporal and spatial resolution and tissue penetration depth. Polymethine cyanine-based dye IR1061 is a typical NIR-II small-molecule organic fluorophore, but its low water solubility and short circulation time limiting its biological applications. Therefore, human serum albumin (HSA) nanoparticles with great biocompatibility and biosafety were employed to fabricate hydrophobic IR1061, which exhibited red-shifted absorption band as typical for J-aggregates. Moreover, IR1061@HSA nanoparticles can be successfully used for NIR-II imaging to noninvasively visualize the tumor vascular networks, as well as real-time intraoperative image-guided tumor resection. Interestingly, benefiting from the high photothermal conversion efficiency brought by J-aggregates, IR1061@HSA nanoparticles were also explored for photothermal therapy (PTT) and cause efficient thermal ablation of tumors. Overall, IR1061@HSA, as a novel J-aggregates albumin-based NIR II dye nanoparticle with high biocompatibility, provides an integrated versatile platform for cancer phototheranostics with promising clinical translation prospects. Graphical abstract: The novel J-aggregates IR1061@HSA nanoparticles have been successfully developed and effectively used for in vivo NIR-II imaging to noninvasively visualize and monitor the tumor vascular networks, as well as real-time NIR-II image-guided intraoperative tumor resection. Moreover, IR1061@HSA nanoparticles have a strong photothermal conversion effect and could thus be an ideal photothermal agent for cancer PTT. Overall, IR1061@HSA, as an albumin-based NIR II dye nanoparticle with high biocompatibility, provides an integrated versatile platform for cancer phototheranostics with promising clinical translation prospects. Image 1